Value Chain Inequality and Its Impact on Salak Pondoh Farmer Share - Sulistriani; Yudi Sapta Pranoto; Yulia (INDONESIAN JOURNAL OF SMALL SCALE FARMING, 2026)
BACKGROUND AND OBJECTIVES The value chain inequality occurs in Pulau Besar Sub-district because the added value generated  during the marketing channel is not evenly distributed between actors. Marketing actors involved in the value chain of salak pondoh commodities in Pulau Besar Sub-district range from farmers and middlemen to retailers. This shows that farmers in Pulau Besar District have a weak bargaining position. So, this study aims to analyze the types of inequality in the salak pondoh value chain and how it impacts farmer share. The results are expected to provide a basis for policymaking and strategies that improve marketing efficiency and farmer empowerment in the local agribusiness system. METHODS   Data collection in this study was carried out using methods such as observation, interviews, and questionnaires. Two approaches in this study are used in data processing methods: descriptive and quantitative. The data analysis method is Farmer's share analysis is done to see the profit or share received by farmers in the form of a percentage. FINDINGS   The distribution of price shares in each channel varies. The pattern of channel l price share received by farmers amounted to 60.10%, channel ll amounted to 71.29%, and channel lll  amounted to 41.04%. This shows the level of inequality in the value received by farmers  compared to the final price at the consumer. In channel ll the inequality is the lowest because farmers receive the largest share. CONCLUSION Farmers are advised to choose marketing channels that provide the highest farmer share and  efficient marketing costs. Based on the study's results, the ll channel is most profitable for farmers. Therefore, farmers are advised to strengthen relationships with retailers and reduce dependence on middlemen. This research can provide useful insights for farmers and salak pondoh business actors.